2008
DOI: 10.1021/jp709613p
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Thermoassociation of Binary Guanosine Gels

Abstract: It is well-known that aqueous solutions of individual guanosine compounds can form gels through reversible self-assembly. Typically, gelation is favored at low temperature and acidic pH. We have discovered that binary mixtures of 5'-guanosine monophosphate (GMP) and guanosine (Guo) can form stable gels at neutral pH over a temperature range that can be tuned by varying the relative proportions of the hydrophobic Guo and the hydrophilic GMP in the mixture. Gelation was studied over the temperature range of 5-40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 32 publications
1
73
0
Order By: Relevance
“…Linear gels are viscous additives that provide good separation performance and do not need to be polymerized in the capillary. Issues associated with the introduction of highly viscous materials into narrow-bore capillaries have spawned the use of thermally reversible sieving materials (76)(77)(78), including phospholipid nanogels (36). These materials are introduced into the capillary at a temperature that generates low viscosity and then converted into a highly viscous separation additive in the capillary by changing the separation temperature.…”
Section: CLmentioning
confidence: 99%
“…Linear gels are viscous additives that provide good separation performance and do not need to be polymerized in the capillary. Issues associated with the introduction of highly viscous materials into narrow-bore capillaries have spawned the use of thermally reversible sieving materials (76)(77)(78), including phospholipid nanogels (36). These materials are introduced into the capillary at a temperature that generates low viscosity and then converted into a highly viscous separation additive in the capillary by changing the separation temperature.…”
Section: CLmentioning
confidence: 99%
“…Previous studies (Yu et al, 2008;Novotná et al, 2012;Lokesh and Suryaprakash, 2013) have shown that the combination of the soluble GMPdss with the relatively insoluble Guo in aqueous solution promotes the formation of cholesteric G4 gels. The present work shows that cholesteric G4 phases are also formed by mixtures of GMP with XMP (X = A, C, G, U) when the two are in different forms (GMPdss/XMPfa or GMPfa/XMPdss).…”
Section: Discussionmentioning
confidence: 98%
“…In the case of GMP, an alternate structure in which the guanines are associated with each other in a continuous helix rather than discrete tetrads has been reported to form in the presence of K + (Walmsley and Burnett, 1999). Higher-order G-tetrad assemblies and gel phases have also been observed in solutions containing mixtures of G-tetrad-forming compounds such as GMP and guanosine (Yu et al, 2008;Novotná et al, 2012;Lokesh and Suryaprakash, 2013) and GMP and isoguanosine phosphate (Roberts et al, 1997). Formation of self-assembled, organized phases (depicted for GMP in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The gel formation processs begins as the quartets assemble into a stack held together, in part, by π-π interactions. As the concentration of guanosine increases, the stacks organize into helical or columnar aggregates that eventually assume a higher ordered crystalline phase or gel (65,66). As with the bilayer electrophoresis discussed in Chapter 4, the electrophoresis of ss-DNA utilizing a G-gel as the separation medium shows that this too is system where specific analyte-"pseudophase" interactions provide for the separation mechanism.…”
Section: Gel Pseudophases (Ch 10)mentioning
confidence: 95%